2018
DOI: 10.1007/s12265-018-9814-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs: a Potential Biomarker for Cardiac Damage, Inflammatory Response, and Left Ventricular Function Recovery in Pediatric Viral Myocarditis

Abstract: Viral myocarditis (VM) can be a life-threatening event resulting in cardiac failure, chronic cardiomyopathy, and death. VM typically includes three phases, i.e., acute, subacute, and resolution/chronic. We prospectively investigated cardiac- and inflammatory-associated plasma-circulating miRNA levels in eight pediatric patients with VM during the three stages of the disease. The level of cardiac-associated miR-208a was significantly elevated during the acute phase compared with the subacute and resolution/chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…In recent years, as a negative regulator of innate immune response, more and more attention has been paid to miRNAs (Mehta & Baltimore, ). Among them, miR‐21 is one of the highest expressed microRNAs in various cell types of mammalian, and its expression is elevated in various diseases such as inflamed tissue (Goldberg et al, ), solid tumors, and cardiac injury (Sheedy, ). Similarly, we also observed that miR‐21 expression was elevated by LPS stimulation compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as a negative regulator of innate immune response, more and more attention has been paid to miRNAs (Mehta & Baltimore, ). Among them, miR‐21 is one of the highest expressed microRNAs in various cell types of mammalian, and its expression is elevated in various diseases such as inflamed tissue (Goldberg et al, ), solid tumors, and cardiac injury (Sheedy, ). Similarly, we also observed that miR‐21 expression was elevated by LPS stimulation compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Liu et al reported that Notoginsenoside R1 protected against oxygen–glucose deprivation‐induced cardiomyocytes damage by rescuing cell viability and suppressing cell apoptosis through up‐regulating miR‐21 expression (Liu et al, ). In addition, Goldberg and his colleagues revealed that the expression of cardiac‐ and inflammatory‐related miR‐21 was remarkably enhanced during the acute phase (Goldberg et al, ). Whereas, whether miR‐21 is associated with the protective effect of Baicalin has never been explored before.…”
Section: Introductionmentioning
confidence: 99%
“…Corsten et al detected increased levels of miR-208b and miR-499-5p in the plasma of 14 patients with acute VMC, which correlated positively with disease severity based on troponin T levels and ejection fraction (134). Furthermore, miR-21 and miR-208a were significantly increased during the acute phase (at admission) in 8 pediatric patients with VMC, and the levels of miR-208a during the subacute phase (9.3 ± 3.4 days from admission) correlated with the degree of recovery of the left ventricular ejection function during the resolution/chronic phase (100.8 ± 35.4 days from admission) (135). However, neither study directly compared miRNA levels with troponin values to identify the superior prognostic marker, and these miRNAs are also elevated in other cardiomyopathies (134).…”
Section: Circulating Mirnas In Myocarditismentioning
confidence: 92%
“…The miR-208 family consisting of miR-208a, miR-208b, and miR-499 direct cardiac myosin gene expression since they are transcribed from the introns of genes encoding the main components of muscle fibers, such as Myh6, Myh7, and Myh7b (133). So far few researches have shown the roles of the miR-208 family in myocarditis other than in other cardiac pathologic conditions, though they have been detected in the plasma of patients with acute myocarditis (134,135).…”
Section: Myomirsmentioning
confidence: 99%
“…Recent studies indicated that miRNAs with specific changes in the progression of heart valve disease play key role in the processes of disease progression, such as fibrosis, calcification, matrix degradation remodeling, and inflammation. In addition, some miRNAs could also regulate extracellular body through exosomes and participate in circulation in the exocrine [21][22][23]. Further studies revealed that these miR-NAs can be used as biomarkers for cardiovascular diseases for clinical diagnosis and personalized medicine.…”
Section: Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%